applyEach ::[(a -> b)]-> a ->[b]
applyEach [] _ =[]
applyEach (f:fs) x = f x : applyEach fs x

applyEach :: [(a -> b)] -> a -> [b]
applyEach [] _ = []
applyEach (f:fs) x = f x : applyEach fs x

This entry was posted on Wednesday, August 8th, 2007 at 10:34 pm and is filed under Uncategorized. You can follow any responses to this entry through the RSS 2.0 feed.
You can leave a response, or trackback from your own site.

applyEach fs x = map (\f -> f x) fs

or using ($)

applyEach fs x = map ($ x) fs